The impact of employee’s recognition, rewards and job stress on job performance. - Cham, Li Wei (2022)
This study is proposed to analyze the impact of employees’ recognition, rewards, and job stress on job performance in Ekovest Company in Kuala Lumpur, Malaysia. 150 questionnaires from the respondents have been collected in this study as the research sample. This study uses quantitative data and multiple-regression for data analysis, including the frequency, reliability, and validity tests. This study suggests that both employee rewards and job stress significantly influence employee job performance. Meanwhile, employees’ recognition does not have a significant influence on employee job performance. This study is expected to provide valuable ideas to Ekovest Company in Malaysia on how to manage their employee rewards better and cope with the stress of employees in the company. However, the results of this study are limited to the sample taken, in which the author suggests using other companies from a different industry sector to conduct future research.